Unified Metrical Common Fixed Point Theorems in 2-Metric Spaces via an Implicit Relation. (20th June 2013) - Chauhan, Sunny; Imdad, Mohammad; Vetro, Calogero
Abstract : We prove some common fixed point theorems for two pairs of weakly compatible mappings in 2-metric spaces via an implicit relation. As an application to our main result, we derive Bryant's type generalized fixed point theorem for four finite families of self-mappings which can be utilized to derive common fixed point theorems involving any finite number of mappings. Our results improve and extend a host of previously known results. Moreover, we study the existence of solutions of a nonlinear integral equation.